SNHG6 203 and SNHG6 201 Transcripts Can be Used as Contributory Factors for a Well-Timed Prognosis and Diagnosis of Colorectal Cancer - Amin Jafari Oliayi; Malek Hossein Asadi (Journal of Kerman University of Medical Sciences, 2018)
Background:Long non-coding RNAs, as a big part of non-coding RNAs, are considered functionally more than past. These transcripts could be involved in carcinogenesis. SNHG6, as a long non-coding RNA, has been reported to be expressed more in colorectal cancer tissues than non-cancerous ones.  Colorectal cancer as a malignancy needs fast prognostic and diagnostic methods for well-timed treatment. SNHG6 RNA and its relative variants can be considered as biomarkers for a well-timed treatment of colorectal cancer. Methods:RNA extraction from 32 colorectal cancer tissues and their relative non-cancerous tissues were carried out and cDNA of the mentioned RNAs was synthesized and RT-qPCR was performed. Relative expression of SNHG6 201 and 203 were studied in colorectal cancer samples with different clinicopathological characteristics. Results:The expression patterns of SNHG6 201 and 203 variants were different. SNHG6 203 was expressed significantly higher in colorectal tumor tissues than non-cancerous ones. In spite of SNHG6 203, SNHG6 201 was expressed significantly in colorectal non-cancerous tissues more than tumor ones. Additionally, expression of these variants in different colorectal cancer cell lines was different. Conclusion:It seems that SNHG6 203 transcript might be considered as a prognostic and diagnostic biomarker in colorectal cancer case studies and treatments. Also, SNHG6 201 can distinguish precisely the tumor and non-tumor tissues in colorectal cancer.